Analysis of The Accuracy of Temperature Sensors at The Calibrator Incubator Laboratory are equipped with data storage base on Internet of Thing - Candra Prastyadi; Bambang Guruh Irianto; Her Gumiwang Ariswati; Dyah Titisari; Steyve Nyatte; Shubhrojit Misra (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
A laboratory incubator is a tool used to incubate or incubate a breed. Incubators provide optimum temperature conditions for microorganisms to grow. The incubator has a temperature regulator so that the temperature can be adjusted according to the breed to be incarnated. Incubators utilize hot-dry like ovens. The purpose of this study is to conduct testing and analyze the accuracy of thermocouple sensors with incubator media in laboratory incubator calibrator tools. The contribution of the research is to know the level of accuracy of the sustainable sensor for sensing the temperature in the lab incubator. The main Design consists of 8 MAX 6675 Standards, 8 Thermocouple type K, Arduino Mega, and SD Card Standards. The temperature not in the incubator device is measured by a Type K thermocouple sensor. Thermocouple sensor numbers 8 channels that measure the temperature at each incubator camber point. The temperature will be stored on the SD card to analyze the data and the data can be processed into the form of a graphic. Benchmarking is done using a data logger temperature tool. This is done to make the Design results are under the standards of the Standard. After comparing with the Standard get the largest error value is 3.98%, at channel T6 temperature 35 °C with ordinary incubator media and the smallest error in ordinary incubator media point T6 temperature 37 ° C which is 0.06 % and in fan incubator temperature 35 C has the largest error which is 2.98 % and the smallest error 0.86%. The conclusion of this study is that the design can work well in measuring the temperature of the incubator, as well as the system for storing readings using the SD card Design and sending data using the internet network can work well.